The labor market in Canada, 2000-2021 - W. Craig Riddell (IZA World of Labor, 2022)
From 2000 to 2019, Canada's economy and labor market performed well. Important in this success was a strong resource boom from the late 1990s to 2014. After the boom the economy and labor market adjusted relatively smoothly, with labor and other resources exiting resource-rich regions and moving elsewhere. Strong growth in major export markets (Asia and the US) aided the adjustment. The Covid-19 downturn resulted in an unprecedented decline in employment, and a steep rise in unemployment and non-participation. Despite the severity of the Covid-19 shock, by December 2021 most key measures of labor market activity had returned to pre-pandemic levels.
Keywords: E24; J6; D6; 330; employment; unemployment; resource boom; real wage growth; inequality; job polarization; Covid-19